Excitation of the precessing vortex core by active flow control to suppress thermoacoustic instabilities in swirl flames. (July 2019) - Lückoff, Finn; Oberleithner, Kilian
In this study, we apply periodic flow excitation of the precessing vortex core at the centerbody of a swirl-stabilized combustor to investigate the impact of the precessing vortex core on flame shape, flame dynamics, and especially thermoacoustic instabilities. The current control scheme is based on results from linear stability theory that determine the precessing vortex core as a global hydrodynamic instability with its maximum receptivity to open-loop actuation located near the center of the combustor inlet. The control concept is first validated at isothermal conditions. This is of utmost importance for the proceeding studies that focus on the exclusive impact of the precessing vortex core on the combustion dynamics. Subsequently, the control is applied to reacting conditions considering lean premixed turbulent swirl flames. Considering thermoacoustically stable flames first, it is shown that the actuation locks onto the precessing vortex core when it is naturally present in the flame, which allows the precessing vortex core frequency to be controlled. Moreover, the control allows the precessing vortex core to be excited in conditions where it is naturally suppressed by the flame, which yields a very effective possibility to control the precessing vortex core amplitude. The control is then applied to thermoacoustically unstable conditions. Considering perfectly premixed flames first, it is shown that the precessing vortex core actuation has only a minor effect on the thermoacoustic oscillation amplitude. However, we observe a continuous increase of the thermoacoustic frequency with increasing precessing vortex core amplitude due to an upstream displacement of the mean flame and resulting reduction of the convective time delay. Considering partially premixed flames, the precessing vortex core actuation shows a dramatic reduction of the thermoacoustic oscillation amplitude. In consideration of the perfectly premixed cases, we suspect that this is caused by the precessing vortex core-enhanced mixing of equivalence ratio fluctuations at the flame root and due to a reduction of time delays due to mean flame displacement.